If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + -5) + 2 = 27 Reorder the terms: -5(-5 + x) + 2 = 27 (-5 * -5 + x * -5) + 2 = 27 (25 + -5x) + 2 = 27 Reorder the terms: 25 + 2 + -5x = 27 Combine like terms: 25 + 2 = 27 27 + -5x = 27 Add '-27' to each side of the equation. 27 + -27 + -5x = 27 + -27 Combine like terms: 27 + -27 = 0 0 + -5x = 27 + -27 -5x = 27 + -27 Combine like terms: 27 + -27 = 0 -5x = 0 Solving -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-5'. x = 0 Simplifying x = 0
| 8.95+1.50=26.95 | | -1.4x=2.67 | | 23/20y=46 | | 0=16x^2-760 | | 6p=-26 | | 5x+4-x-1= | | 3b-15=12 | | 40x^2+2x-30=0 | | =10x^2+3x-1 | | 3(3z-2)-3(2-2z)=6 | | 4x^2=75 | | 4=-5x+4(x+4) | | 10y+5x=12 | | 102+4n=1486 | | -2a+6=2a-2 | | 8x^2-17x-671=0 | | -19.76x=-92.57x | | -6k-3=33 | | 9x-21=35-1 | | 227x=1052x | | 3x+2=3(5)+2 | | .53a=.06a+.4 | | -19.76x+227=-92.57+1052 | | 5=7+-2h | | 9(k+5)=-6 | | 20=-0.5x-10 | | -3f-11=13 | | 2p-5(p-40)=2p+15 | | n=24.2-3.8 | | 5x^2+11x+17=0 | | 4x-147-12x=53 | | -5x+2(6x-14)=14 |